Synthesis, Structural, and Antimicrobial Studies of Some New Coordination Compounds of Palladium(II) with Azomethines Derived from Amino Acids - Monika Gupta; Sangeeta Sihag; A. K. Varshney; S. Varshney (Journal of Chemistry)
Some new coordination compounds of palladium(II) have been synthesized by the reaction of palladium(II) acetate with azomethines in a 1 : 2 molar ratio using acetonitrile as a reaction medium. Azomethines used in these studies have been prepared by the condensation of 2-acetyl fluorene and 4-acetyl biphenyl with glycine, alanine, valine, and leucine in methanol. An attempt has been made to probe their bonding and structures on the basis of elemental analyses and IR, 1H, and 13C NMR spectral studies. Pd(II) compounds have been found to be more active than their uncomplexed ligands as both of them were screened for antibacterial, antifungal, and insecticidal activities.